2018
DOI: 10.1002/ecy.2192
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐guild herbivory disrupts predator‐prey interactions in the field

Abstract: Plant defenses often mediate whether competing chewing and sucking herbivores indirectly benefit or harm one another. Dual-guild herbivory also can muddle plant signals used by specialist natural enemies to locate prey, further complicating the net impact of herbivore-herbivore interactions in naturally diverse settings. While dual-guild herbivore communities are common in nature, consequences for top-down processes are unclear, as chemically mediated tri-trophic interactions are rarely evaluated in field envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 84 publications
(141 reference statements)
0
24
0
Order By: Relevance
“…HIPVs can also be detected by neighboring plants and help them to anticipate an incoming attack ( Arimura et al, 2000 ; Heil and Ton, 2008 ; Engelberth et al, 2004 ; Karban et al, 2014 ; Sugimoto et al, 2014 ; Nagashima et al, 2018 ). Hence, HIPVs provide information to all players in a plant’s ecological network and through these various effects, HIPVs play a major role in determining the composition of insect communities in the field ( Xiao et al, 2012 ; Zhu et al, 2015 ; Poelman and Dicke, 2014 ; Blubaugh et al, 2018 ; Schuman and Baldwin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIPVs can also be detected by neighboring plants and help them to anticipate an incoming attack ( Arimura et al, 2000 ; Heil and Ton, 2008 ; Engelberth et al, 2004 ; Karban et al, 2014 ; Sugimoto et al, 2014 ; Nagashima et al, 2018 ). Hence, HIPVs provide information to all players in a plant’s ecological network and through these various effects, HIPVs play a major role in determining the composition of insect communities in the field ( Xiao et al, 2012 ; Zhu et al, 2015 ; Poelman and Dicke, 2014 ; Blubaugh et al, 2018 ; Schuman and Baldwin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A competing chewing herbivore might dilute or constrain volatile signals exploited by aphid parasitoids to find their prey ( Vos et al, 2001 ), reducing top–down suppression. Indeed, our recent fieldwork in this system showed that co-herbivory by chewing herbivores reduced aphid parasitism as well as concentrations of secondary metabolites important in aphid-specific volatile signaling ( Blubaugh et al, 2018 ). This consistent pattern detected across a gradient of microbial diversity further emphasizes the importance of herbivore community structure in determining the outcome of tritrophic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…capitata, cvs. Arcadia) are attacked by herbivorous aphids and caterpillars, while the aphids (but generally not the caterpillars) are in turn attacked by parasitoid wasps ( Snyder et al, 2006 ; Blubaugh et al, 2018 ). The cabbage aphid ( Brevicoryne brassicae ) is the dominant aphid on these plants, while Pieris rapae is the most common caterpillar species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open questions include whether natural enemies affect the strength or outcome of plant‐mediated herbivore interactions (e.g. De Rijk et al ; Blubaugh et al ), and whether plant indirect defence traits affect apparent competition among herbivores when the latter share enemies.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%